Reconstructing Indonesia’s Legislative Politics Following Constitutional Court Decision No. 91/PUU-XVIII/2020: Between the Omnibus Law, Legislative Delegation, and Constitutional Control: Rekonstruksi Politik Legislasi Indonesia Setelah Putusan MK NO. 91/PUU-XVIII/2020: Antara Omnibus Law, Delegasi Legislasi, dan Kontrol Konstitusional - Prasetyoningsih, Nanik; Wardhana, Allan Fatchan Gani (Universitas Islam Indonesia, 2025)
Constitutional Court Decision No. 91/PUU-XVIII/2020 marked a significant turning point in Indonesia’s legislative politics. For the first time, the Court declared a statute conditionally unconstitutional on the grounds of procedural defects, while simultaneously affirming the importance of meaningful public participation and due process in law-making. Nevertheless, subsequent developments have revealed an ambivalent trajectory. The Government issued Government Regulation in Lieu of Law No. 2 of 2022, which was later enacted as Law No. 6 of 2023, while the amendment to the Law on the Formation of Laws and Regulations through Law No. 13 of 2022 effectively institutionalized the omnibus method as a permanent legislative technique. This article examines the reconstruction of Indonesia’s legislative politics following Constitutional Court Decision No. 91/2020, particularly in relation to the omnibus law method, legislative delegation, and constitutional control. It employs a normative juridical method with statutory, conceptual, and case-based approaches, drawing on an analysis of the 1945 Constitution, the Job Creation Law, the Law on the Formation of Laws and Regulations, the Government Regulation in Lieu of Law on the Job Creation, and relevant Constitutional Court decisions issued after 2020. The study identifies three principal tendencies. First, the omnibus method has undergone a process of normalization within Indonesia’s legislative framework. Second, delegated legislation has reinforced a pattern of executive-heavy law-making, shifting substantial normative authority toward the executive branch. Third, constitutional control over formal judicial review remains inconsistent in its application. At the same time, although the Constitutional Court has normatively strengthened the principle of public participation, such participation has not yet been adequately institutionalized in legislative practice. This article argues that the reconstruction of Indonesia’s legislative politics should be directed toward limiting the use of the omnibus method, tightening the scope of normative delegation, strengthening meaningful public participation, and developing more robust mechanisms of checks and balances and constitutional dialogue. Such measures are necessary to ensure that the legislative process is brought back into alignment with the principles of the rule of law and constitutional democracy.